Strategy For Parents Assistance in Early Children's Learning Based on Virtuil Class of TV Sekolah - Husnawati Husnawati; Sri Watini; Arianty Arianty; Cucun Cunaya; Halifa Rahakbauw (International Conferences on Early Childhood Education Proceedings, 2023)
Parents are the first and foremost educators for children. Parental assistance in the child's learning process is the effort of parents to accompany, provide assistance in overcoming children's learning problems, provide encouragement, motivation, support, supervision and provide facilities for children to be enthusiastic in learning to achieve achievements. The purpose of this research is to describe the strategy for assisting parents in the learning process in virtual PAUD classroom-based TV schools which are implemented in several regions in Indonesia, including: Garut, Bekasi, Banten, Tangerang, DKI Jakarta and Papua. The learning process in early childhood needs to collaborate harmoniously between children, teachers and parents as companions. Companion in this case the parents have a very important role. This is in line with the Tri Center for Education which was initiated by Ki Hajar Dewantara that education must involve three environments, namely the family, school and community environment. The method used is descriptive qualitative research, with interviews, observation and documentation techniques. The research was conducted from December 2022 to February 2023. This research describes the steps in the process of assisting parents when accompanying their children to learn using school TV-based virtual classroom media from the preparation, implementation and evaluation stages. Through this assistance, the material is studied, the time used in learning, the evaluation process is all guided and always under the supervision of parents. The findings from this study indicate that the Virtual TV School class is a new breakthrough in the world of education where parents play an active role in assisting learning for early childhood.